Innovative Lightweight Concrete with Carbonated Magnesium-Based Pellets - Sahin, Onur; Coskun, Enis; Akca, Abdullah Huzeyfe (MDPI, 2026)
The construction industry requires sustainable building materials to reduce its environmental impact. While using these materials in newly constructed structures primarily focuses on environmental benefits, their application in the protection of architectural heritage presents an additional requirement. These materials must be physically and chemically compatible with historical substrates to ensure the longevity of the structure. Therefore, developing eco-friendly and compatible restoration materials is a significant concern. This study aims to produce artificial aggregates to develop lightweight concrete for structural interventions and reduce natural resource consumption (i.e., minimizing the destructive extraction of natural river sand and crushed stone aggregates). Magnesium-based binders were used to mimic the carbonation process of historical lime mortars. The binders were mixed with water, shaped into coarse pellets, and cured in a CO2 incubator for 3 and 14 days before being used in concrete production. The results show that using artificial aggregates decreased the concrete density by approximately 16.5%. Since reducing the dead load improves the seismic safety of historical masonry structures, this reduction is critical. Although the compressive strength decreased compared to natural aggregate concrete, the 14-day cured series achieved a strength of 34.7 MPa. This demonstrates that the material can be used in restoration interventions where stiffness compatibility is essential (e.g., vault infills, ring beams, or floor screeds). At the same time, since magnesium-based artificial lightweight pellets have CO2 sequestration capacity, they can be used as a carbon-negative solution for both historical structures and broader civil infrastructure.
Keywords: magnesium oxide; artificial aggregates; compressive strength; carbonation; FLY-ASH; THERMAL-DECOMPOSITION; PELLETIZATION PROCESS; AGGREGATE; CONSTRUCTION; DESALINATION; ENERGY; Chemistry; Materials Science; Metallurgy & Metallurgical Engineering; Physics